Rationale, design and study protocol of the randomised controlled trial: Diabetes Interventional Assessment of Slimming or Training tO Lessen Inconspicuous Cardiovascular Dysfunction (the DIASTOLIC study). Issue 3 (30th March 2019) - Gulsin, Gaurav Singh; Brady, Emer M; Swarbrick, Daniel J; Athithan, Lavanya; Henson, Joseph; Baldry, Emma; McAdam, John; Marsh, Anna-Marie; Parke, Kelly S; Wormleighton, Joanne V; Levelt, Eylem; Yates, Thomas; et al.
Abstract : Introduction: Despite their young age and relatively short duration of disease, younger adults with type 2 diabetes (T2D) already have diastolic dysfunction and may be at risk of incipient heart failure. Whether weight loss or exercise training improve cardiac dysfunction in people with T2D remains to be established. Methods and analysis: Prospective, randomised, open-label, blind endpoint trial. The primary aim of the study is to determine if diastolic function can be improved by either a meal replacement plan or a supervised exercise programme, compared with guideline-directed care. A total of 90 obese participants with T2D (aged 18–65 years), diabetes duration <12 years and not on insulin treatment will be randomised to either guideline-directed clinical care with lifestyle coaching, a low-energy meal replacement diet (average ≈810 kcal/day) or a supervised exercise programme for 12 weeks. Participants undergo glycometabolic profiling, cardiopulmonary exercise testing, echocardiography and MRI scanning to assesses cardiac structure and function and dual-energy X-ray absorptiometry scanning for body composition. Key secondary aims are to assess the effects of the interventions on glycaemic control and insulin resistance, exercise capacity, blood pressure, changes in body composition and association of favourable cardiac remodelling with improvements in weight loss, exercise capacity and glycometabolic control. Ethics and dissemination: The study has full ethical approval, and data collection was completed in August 2018. The study results will be submitted for publication within 6 months of completion. Trial registration number: NCT02590822; Pre-results.